Digital finance and agri-food value chains: Case studies from Nigeria - Russel, Yeshua (International Food Policy Research Institute, 2025)
Nigeria’s agri-food sector is one of the largest and most complex in sub-Saharan Africa, encompassing diverse crops, regions, actors, and markets. With agriculture contributing approximately 24% to the national GDP and employing over 70% of the rural workforce (CBN, nd), the sector plays a central role in livelihoods, food security, and inclusive growth. Within this sector, agri-food value chains constitute the connective tissue that links smallholder farmers, processors, traders, input suppliers, and consumers, both within the domestic economy and across international markets.